Information literacy in the workplace - Forster, Marc (Librarian) (London : Facet, 2017)
This book explains how information literacy (IL) is essential to the contemporary workplace and is fundamental to competent, ethical and evidence-based practice. In today's information-driven workplace, information professionals must know when research evidence or relevant legal, business, personal or other information is required, how to find it, how to critique it and how to integrate it into one's knowledge base. To fail to do so may result in defective and unethical practice which could have devastating consequences for clients or employers. There is an ethical requirement for information professionals to meet best practice standards to achieve the best outcome possible for the client. This demands highly focused and complex information searching, assessment and critiquing skills.
Foreword / Jane Secker -- 1. Information Literacy and the workplace : new concepts, new perspectives? / Marc Forster -- 2. How is Information Literacy experienced in the workplace? / Marc Forster -- 3. Information Literacy and the personal dimension : team players, empowered clients and career development / Marc Forster -- 4. From transaction to transformation : organizational learning and knowledge creation experience within informed systems / Mary M. Somerville and Christine S. Bruce -- 5. Virtuality at work : an enabler of professional Information Literacy / Elham Sayyad Abdi -- 6. Determining the value of Information Literacy for employers / Stéphane Goldstein and Andrew Whitworth -- 7. Information Literacy's role in workplace competence, 'best practice' and the ethics of professional obligation / Marc Forster -- 8. Learning within for beyond : exploring a workplace Information Literacy design / Annemaree Lloyd -- 9. Developing information professional competences in disciplinary domains : a challenge for higher education / Stephen Roberts -- 10. The 'hidden' value of Information Literacy in the workplace context : how to unlock and create value / Bonnie Cheuk -- 11. The 'Workplace Experience Framework' and evidence-based Information Literacy education / Marc Forster -- References - Index.
Title from publisher's bibliographic system (viewed on 05 Jul 2018).
Keywords: Information literacy; Workplace literacy